PENGARUH MODEL PEMBELAJARAN CONNECTING ORGANIZIG REFLECTING EXTENDING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII - Bokari, Nabilla Resta (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematicaliiproblem-solving skills are one of the skills that students must master. But their math problem-solving skills aren't the best. This is because the learning model used failed to develop students' math problem-solving skills. Implementation of the Connecting,Organizing,  Reflecting,  Extending (CORE) learning model can be used to improve students' math problem-solving abilities. The achievement of this research is to see students' ability to solve math problems by applying the CORE model were superior to those of students learning in direct learning. Based on this research, we know that students learning with CORE are superior in solving math problems than those using direct learning models.Keywords. – Connecting Organizing Reflecting Extending, Mathematical problem-solving skills.